Designing a Smart Inverter for Voltage Sag Compensation Due to Motor Start-up - Budi Hermawan, Indra; Mochamad, Ashari; Candra Riawan, Dedet (Universitas Muhammadiyah Malang, 2023)
Starting a large induction motor will always follow up with an inrush current as the nature of an induction motor. On a less stiff power system, that inrush current will be causing a Voltage Sag (VS). A big VS can lead to significant disruptions in power quality and reliability. To address this, a Smart Inverter with an Artificial Intelligence (AI) -driven controller installed in a Photovoltaic (PV) farm is proposed for voltage sag recovery. During normal conditions, the PV farm acts as a power source supporting the main grid, but when large induction motors are started, the smart inverter connected to the PV is responsible for power conversion to recover sags caused by the Induction motor inrush current. The controller inside the Inverter ensures optimal operation. The use of AI also compares the effectiveness of using the Fuzzy Logic Controller (FLC) with the Proportional Integral (PI) Controller to assess their performance in reducing current spikes. Based on simulations, the FLC outperformed PI Controller in mitigating the voltage sag and avoiding the Low Voltage Ride-Through (LVRT). Simulation results show that voltage sag can be recovered for up to 97% of the nominal voltage, a significant improvement over the 80% sag recovery without the smart Inverter. At a nominal grid voltage of 6,600 volts, the VS Magnitude was successfully increased from 5,210 volts to 6,368 volts and the VS Duration also decreased from 6.96 s to 4.97 s. The results achieved validate the effectiveness of the approach in improving the power quality.